A companion to Alfred Hitchcock - Leitch, Thomas M.; Poague, Leland A., 1948-; Blackwell Reference Online (Online service) (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2011)
"Alfred Hitchcock remains the quintessential cinematic auteur - the director as hero. Fifty years of debate over his status as an obsessive and dictatorial artist has raised increasingly pressing questions about the relation between individual authorship, on the one hand, and contexts, influences, and collaborators, on the other. A Companion to Alfred Hitchcock authoritatively maps the body of work generated in response to the director and his films, compiling essays from some of the world's most noted scholars in the emerging field of Hitchcock studies"--
pt. I Background : Hitchcock's lives / Thomas Leitch -- Hitchcock's literary sources / Ken Mogg -- Hitchcock and early filmmakers / Charles Barr -- Hitchcock's narrative modernism : ironies of fictional time / Thomas Hemmeter -- pt. II Genre : Hitchcock and romance / Lesley Brill -- Family plots : Hitchcock and melodrama / Richard R. Ness -- Conceptual suspense in Hitchcock's films / Paula Marantz Cohen -- pt. III Collaboration : "Tell me the story so far" : Hitchcock and his writers / Leland Poague -- Suspicion : collusion and resistance in the work of Hitchcock's female collaborators / Tania Modleski -- A surface collaboration : Hitchcock and performance / Susan White -- pt. IV Style : Aesthetic space in Hitchcock / Brigitte Peucker -- Hitchcock and music / Jack Sullivan -- Some Hitchcockian shots / Murray Pomerance -- pt. V Development : Hitchcock's silent cinema / Sidney Gottlieb -- Gaumont Hitchcock / Tom Ryall -- Hitchcock discovers America : the Selznick-era films / Ina Rae Hark -- From transatlantic to Warner Bros. / David Sterritt -- Hitchcock, metteur-en-scène : 1954-60 / Joe McElhaney -- The universal Hitchcock / William Rothman -- pt. VI Auteurism : French Hitchcock, 1945-55 / James M. Vest -- Lost in translation? Listening to the Hitchcock-Truffault interview / Janet Bergstrom -- Robin Wood's Hitchcock / Harry Oldmeadow -- pt. VII Ideology : Accidental heroes and gifted amateurs : Hitchcock and ideology / Toby Miller, with Noel King -- Hitchcock and feminist criticism : from Rebecca to Marnie / Florence Jacobowitz -- Queer Hitchcock / Alexander Doty -- pt. VIII Ethics : Hitchcock and philosophy / Richard Gilmore -- Hitchcock's ethics of suspense : psychoanalysis and the devaluation of the object / Todd McGowan -- Occassions of sin : the forgotten cigarette lighter and other moral accidents in Hitchcock / George Toles -- pt. IX Beyond Hitchcock : Hitchcock and the postmodern / Angelo Restivo -- Hitchcock's legacy / Richard Allen.
Includes bibliographical references and index.
Print version record.
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation; Hitchcock, Alfred, -- 1899-1980.; Hitchcock, Alfred, -- 1899-1980.; Hitchcock, Alfred, -- 1899-1980.; PERFORMING ARTS -- Film & Video -- History & Criticism; Electronic books; Criticism, interpretation, etc